THE STABILITY OF SOME SPRING TRITICALE GENOTYPES USING BIPLOT ANALYSIS - E. Kendal; M. S. Sayar (Journal of Animal and Plant Sciences, 2016)
This research examined the adaptability of triticale genotypes in three sub-regions of Southeastern Anatolia that represent distinct agro ecological zones. The study was conducted using a total of 25 genotypes, including 20 advanced lines, three triticale varieties, one durum wheat variety, and one bread wheat variety. Yield and crop quality traits for these genotypes were assessed at four locations over the 2010–2011 growing season. The stability and superiority of genotypes were assessed in terms of crop traits including grain yield, yield components, and crop quality parameters using GGE biplot analysis. Three study locations showed distinct traits: Diyarbakir was found to be the most suitable overall location with a high stability value, Kızıltepe showed high grain yield, and Mardin showed superior crop quality traits. However, when all crop traits were analyzed with respect to location, crop quality parameters formed the first group, plant height (PH) and grain yield (GY) formed the second group, and heading time (HT) formed a third group. When the parameters were analyzed for genotypes, three different groups were formed, in which grain yield and thousand-grain weight (TGW) formed the first group, protein content (PC) and test weight (TW) formed the second group, HT and PH formed the third group. Consequently, the Sarıçanak 98 (durum wheat) and Nurkent (bread wheat), which are referred to as standard varieties in this study, as well as genotype lines 3, 7, 12, 13, 16, and 21 were considered suitable for cultivation in Southeastern Anatolia, whereas the remaining genotypes were below average with respect to overall performance. Furthermore, we found that the GGE biplot method generated highly useful results with high visual quality.
Keywords: GGE Biplot; Genotype × environment interaction; Spring Triticale; Turkey